Terpyridine-Containing π-Conjugated Polymers for Light-Emitting and Photovoltaic Materials - Liu, Pan; Shi, Ganhui; Chen, Xuegang (Frontiers in Chemistry, 2020)
2,2´:6´,2´´-Terpyridine is versatile moiety for construct abundant novel small molecules or polymers. Extending or coupling with the π-conjugation structures can bring some interesting opto-elctronical properties. This mini-review summarized the significant progress of the terpyridine-containing π-conjugated polymers for light-emitting and photovoltaic materials for the past decades. Coordinating with metal ions, terpyridine exhibits large potentialities for creating metallo-supramolecular or metallo-polymer materials, therefore, much attention has been paid to the terpyridine-based metallo-polymers and selected examples will be described. A special emphasis on discussion about properties of these functional systems opens prospects for their application in light-to-electricity or electricity-to-light conversion fields.